Integration of Chitosan and Sugar Cane Bagasse as Adsorbent for Remazol Red Dyes Removal - Hamzah, Sofiah; Abdullah, Siti Nadhirah; Mohammad, Nurul Aqilah; Che Harun, Mohammad Hakim; Hairom, Nur Hanis Hayati; Abd. Rahman Azmi, Alyza Azzura; Ali, Asmadi; Ali, Nora’aini; Yatim, Norhafiza Ilyana (2023)
In this study, the sugarcane bagasse biomass was modified and purpose as a bio-adsorbent to remove Remazol red dye from wastewater. The sugarcane bagasse was calcined at 200˚C, followed by the treatment with 1% chitosan solution. The adsorbent was morphologically characterized using FTIR, SEM, XRD analysis to study further the effect of chemical modification techniques on calcined biomass of sugarcane bagasse. Treated calcined sugarcane showed an irregular surface and appearance of pores effects of an acidic chitosan solution. It also clarified the presence of an active site for dye absorption on the adsorbent's surface, which is necessary for the dye adsorption attachment site. The adsorption performance revealed that treated sugarcane bagasse performed better with an optimum adsorbent dosage of 150 mg at an equilibrium time of 60 min. Remazol Red removal favored acidic conditions at pH 4 and decreased as dye concentration increased. With an R2 value, the equilibrium data adsorption fitted well with the Langmuir adsorption isotherm.